Pacific economic monitor (Asian Development Bank, 2020)
TThis latest issue of the Pacific Economic Monitor highlights the gains of Pacific developing member countries (Pacific DMCs) and the challenges that the Pacific DMCs continue to face including the impacts of climate change.